Injection propofol and ketamine in pediatric and adult patients undergoing diagnostic radiological procedure (magnetic resonance imaging and computed tomography scan) - Agrawal, Mahendra; Gandhi, Pushpal; Agrawal, Bhavika; Behl, Simarn (International Journal of Research in Medical Sciences, 2020)
Background: The purpose of this study was to evaluate the effect of propofol and ketamine in pediatric and adult patients undergoing diagnostic radiological procedure (magnetic resonance imaging (MRI) and computed tomography (CT) scan). Methods: A comparative observation study conducted at Sri Aurobindo Medical College and PG Institute, Indore, Department of Anesthesiology after approval from Institutional ethical committee. The duration of this study was April 2019 to May 2020. Group KP: Inj. combination of ketamine and propofol (ketofol) with bolus dose of 0.50 mg/kg and 0.75 mg/kg respectively in initial 10 min followed by infusion at the rate of 0.05 ml/kg/hr till the completion of imaging. Results: The mean age was 11.55±2.80 in children and 31.34±2.43 in adult. Mean weight of patients were 30.54±8.86 in children and 60.21±10.45 in adult. Gender distribution (male:female) were 24/16 and 26/14 children group and adult group. Conclusions: We found that the combination of ketamine (ketofol) and propofol to be safe and well tolerated in pediatric patients and adult patients undergoing diagnostic radiological procedure (MRI and CT scan).